STRATEGI INTENSIF UNTUK MENUMBUHKAN DAYA SAING STUDI KASUS DI URBANHIJAB INDONESIA - Riana, Dwi (Universitas Muhammadiyah Palembang, 2017)
Purpose - The purpose of this research was urbanhijab how to improve the profitability and growth fastly of the brand in the eyes of customers and only has one store in Palembang.Design/methodology - To overcome these problems, Urbanhijab Indonesia analyze both external and internal environment. These factors are outlined in the SWOT analysis showed strength, weaknesses, opportunities and threats for Urbanhijab Indonesia, then formulated into the analysis to EFAS (External Factor Analysis Summary), IFAS (Internal Factor Analysis Summary) and SFAS (Strategic Factor Analysis Summary). Findings – Based on the results of EFAS and IFAS, which were formulated and then use IE Matrix to show Urbanhijab Indonesia position, which is on the first cell (growing concentration through integration). After that, in order to determine which strategy is most interesting between intensive or integrative analysis, the author is doing The Quantitative Strategic Planning Matrix (QSPM). The most attractive strategy is the intensive strategy, which consists of market penetration, market development, and product development. Furthermore, Urrbanhijab Indonesia will make a wabsite for market development.